2016
DOI: 10.4081/monaldi.2006.582
|View full text |Cite
|
Sign up to set email alerts
|

Pleural tuberculosis

Abstract: Pleural effusions in tuberculosis are commonly seen in young adults as an immunological phenomenon occurring soon after primary infection. However, the epidemiology and demographics of tuberculous pleurisy are changing due to the impact of HIV co-infection and the increasing number of pleural effusions seen as part of re-activation disease. Pleural biopsy for histology and culture is the mainstay of diagnosis with closed needle biopsy adequate in the majority of cases. Techniques such as PCR of biopsy specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…In this study, the two study groups were different in age and chronic diseases, such as diabetes, arrhythmia, coronary heart disease, chronic gastritis. One study indicated that pleural tuberculosis was most commonly seen in adolescents and young adults (28), which was similar with this study. Another study found out that, compared with tuberculosis patients who had diabetes, the incidence of pleurisy is reduced in the tuberculosis patients who do not have diabetes (29).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the two study groups were different in age and chronic diseases, such as diabetes, arrhythmia, coronary heart disease, chronic gastritis. One study indicated that pleural tuberculosis was most commonly seen in adolescents and young adults (28), which was similar with this study. Another study found out that, compared with tuberculosis patients who had diabetes, the incidence of pleurisy is reduced in the tuberculosis patients who do not have diabetes (29).…”
Section: Discussionsupporting
confidence: 90%
“…It is hypothesized that TB can be the culprit of up to 80% of pleural effusions in these locations [ 8 ]. The epidemiology and traditional demographics of TB haVe been shifting with more data showing increased presence with HIV co-infection and those that are immunosuppressed [ 9 ]. PT is the most common extrapulmonary form in adults [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…When pus is obtained on thoracentesis, a definitive diagnosis of pyothorax is made. When the protein level in nonpurulent pleural effusion is high, tuberculous pleuritis should be differentiated [244].…”
Section: [Characteristics and Classification Of The Disease]mentioning
confidence: 99%